2007
DOI: 10.1177/0309133307076485
|View full text |Cite
|
Sign up to set email alerts
|

The sediment delivery problem revisited

Abstract: Understanding the sediment delivery process at the drainage basin scale remains a challenge in erosion and sedimentation research. In the absence of reliable spatially distributed process-based models for the prediction of sediment transport at the drainage basin scale, area-specific sediment yield (SSY; t km—2 y—1) is often assumed to decrease with increasing drainage basin area (A). As the measurement of A is relatively simple, this assumption is frequently used for prediction of SSY in ungauged basins. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
205
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 371 publications
(220 citation statements)
references
References 67 publications
8
205
4
3
Order By: Relevance
“…Robinson 1977). This approach has, however, received a lot of criticism, mainly due to its black box nature (Walling 1983;de Vente and Poesen 2005;de Vente et al 2007). Especially in (semi)-arid and Mediterranean environments (i.e.…”
Section: Ii1 Scale Dependency Of Soil Erosion Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Robinson 1977). This approach has, however, received a lot of criticism, mainly due to its black box nature (Walling 1983;de Vente and Poesen 2005;de Vente et al 2007). Especially in (semi)-arid and Mediterranean environments (i.e.…”
Section: Ii1 Scale Dependency Of Soil Erosion Processesmentioning
confidence: 99%
“…environments with a potential desertification risk) SDRs are hard to apply, as they are very variable and difficult to assess. Studies of A-SY relationships for various (semi-)arid regions indicated both negative trends, with often much stronger decrease of SY with A than in humid regions, as well as insignificant or even positive relationships (Walling & Kleo 1979;Verstraeten et al 2006;de Vente et al 2007). In a study of SY and its scale dependence in Europe, Vanmaercke et al (2010a subm.…”
Section: Ii1 Scale Dependency Of Soil Erosion Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Descheemaeker et al 2006;Haregeweyn et al 2008;Nyssen et al 2009a), the integrated effect of these measures at the medium-sized catchment scale is not well understood. The response of catchments to soil erosion and human interventions is often complex due to scale effects which can buffer changes in sediment supply (Walling 1983;Trimble 1999;Verstraeten et al 2002;Walling 2006;de Vente et al 2007). Further, many rivers in the northern Ethiopian highlands have a hydrological regime characterized by flash floods.…”
Section: Introductionmentioning
confidence: 99%